Active inhibition of task-irrelevant sounds and its neural basis in patients with attention deficits after traumatic brain injury. (October 2014) - Sawamura, Daisuke; Ikoma, Katsunori; Yoshida, Kazuki; Inagaki, Yuji; Ogawa, Keita; Sakai, Shinya
Abstract Primary objective: To examine active inhibition of irrelevant stimuli and evaluate its neural basis using functional near infrared spectroscopy in patients with attention deficits after traumatic brain injury (TBI). Research design: Case control study. Methods and procedures: Ten patients with TBI and 10 healthy control subjects participated in this study. The Paced Auditory Serial Addition Test (PASAT) was performed with (distracting PASAT) and without (PASAT) distracting Japanese kana phonetic characters presented between each number. A block design was used. Subjects alternately performed each task three times. Main outcomes and results: Healthy controls performed better than patients with TBI on both the tasks. When performing the PASAT, healthy controls showed significant activity in every region of interest except the right lateral prefrontal cortex (PFC), but patients with TBI showed significant activity only in the left anterior PFC and left lateral PFC. When performing the distracting PASAT, the right lateral PFC was active in healthy controls, but not in patients with TBI. Conclusion: These results confirm that patients with moderate-to-severe TBI were affected by distractors that influenced order processing. It is suggested that the working memory of patients with TBI was affected by distracting stimuli, whereas that of healthy individuals was not.